Effect of a strong axial magnetic field in the plasma recombination and extreme ultraviolet emission from a highly-ionized capillary discharge - Lehmann, Frank J., author; Villagran, Mayo, author; Schmerge, John F., author; Rocca, Jorge J., author; Marconi, Mario Carlos, author; IEEE, publisher (Colorado State University. Libraries, 1990)
The effect of an externally-applied 70-100 kG axial magnetic field in the temporal evolution of the extreme ultraviolet emission from a 500 μm diameter highly-ionized LiH capillary discharge has been studied. In the absence of external magnetic confinement, strong emission from ionic transitions excited by collisional recombination is observed at the end of the current pulse. The externally-applied magnetic field is observed to reduce the intensity of the recombination lines by decreasing the rate of plasma cooling by electron heat conduction to the capillary walls. In contrast, the self-generated magnetic field of the discharge aids to the generation of an initially hot plasma, and allows rapid conduction cooling at the end of the current pulse. The results are discussed in relation to a proposed capillary-discharge-excited extreme ultraviolet recombination laser scheme.
Keywords: plasma transport processes; ion lasers; ion recombination; magnetic field effects; discharges (electric); plasma collision processes